Acute renal insufficiency and pancreatitis in a child with atypical Henoch–Schönlein purpura: efficacy of a single dose of cyclophosphamide - Cristina Maggio, Maria (J Int Med Res, 2018)
A 9-year-old boy with petechiae on the legs and abdominal pain was unsuccessfully treated with steroids. He was admitted to our hospital for the onset of fever, ecchymosis, and arthralgia. Skin lesions suggested vasculitis, but they were not typical of Henoch–Schönlein purpura. He showed ecchymosis of the scrotal bursa, diffusion of petechiae to the trunk and arms, vomiting, severe abdominal pain, oliguria with hyponatremia, hypoalbuminemia, low C3 levels, high levels of creatinine, blood urea nitrogen, and tubular enzymes, proteinuria, and glycosuria. The urinary sediment showed macrohaematuria, and hyaline and cellular casts. Ultrasound showed polyserositis. He was treated with intravenous furosemide, albumin, and methylprednisolone. He underwent colonoscopy and gastroscopy because of development of acute pancreatitis and severe anaemia. Typical lesions of Henoch–Schönlein purpura were observed in the small intestine and colon mucosa. He received three high doses of methylprednisolone, followed by intravenous cyclophosphamide. A dramatic and persistent response was observed after these doses. A single high dose of cyclophosphamide is appropriate in Henoch–Schönlein purpura with acute renal failure and severe pancreatitis that are non-responsive to high-dose steroids.